High-performance crucible coating for large-diameter monocrystalline silicon and preparation method of high-performance crucible coating

By using Al2O3 and boron nitride co-thermal method in the quartz crucible coating, and introducing carbon powder to form Al-C bonds, combining technical means such as alcoholization treatment, silane coupling agent treatment and magnesium powder to generate MgO, the problems of uneven thermal stress distribution, insufficient corrosion resistance and low bonding strength of the existing coating in high temperature environments are solved, and the high mechanical strength, thermal conductivity and high temperature corrosion resistance of the coating are improved.

CN119799047AActive Publication Date: 2025-04-11BEIJING BEIYUAN SEMICONDUCTOR TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510311584.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing quartz crucible coating has uneven thermal stress distribution in high temperature environments, resulting in bulging or cracks; insufficient corrosion resistance and is susceptible to oxygen and impurities; low binding strength, easy to peel or fall off; complex preparation process and high cost.

Method used

Aluminum nitride was prepared as the main material by co-thermal method of Al2O3 and boron nitride, and excessive carbon powder was introduced to form Al-C bonds to enhance high-temperature resistance and structural stability; surface adsorption was improved by alcoholization treatment and silane coupling agent treatment; magnesium powder was introduced to generate MgO to improve temperature resistance and corrosion resistance; a continuous film layer was formed using silica sol and anhydrous ethanol, and polyethylene glycol and aluminum phosphate were added to enhance adhesion and structural stability.

Benefits of technology

The mechanical strength, thermal conductivity and high-temperature corrosion resistance of the coating are significantly improved, and the coating is removed and the bulging or cracks of the quartz crucible are avoided, which extends the service life and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799047A_ABST
    Figure CN119799047A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coating materials, and particularly relates to a high-performance crucible coating for large-diameter monocrystalline silicon and a preparation method thereof.The high-performance crucible coating for the large-diameter monocrystalline silicon is prepared from, by weight, 10-15 parts of a coating compound, 5-8 parts of a compound colloidal substance, 1 part of magnesium powder, 2-5 parts of SiC and 0.5 part of quartz fiber; according to the invention, aluminum nitride obtained by co-heating Al2O3 and boron nitride is used as a main body, and carbon powder is added to form an Al-C bond, so that the high temperature resistance is enhanced, and the structure is stabilized; by adding magnesium powder to remove oxygen, MgO is generated at the same time, so that the temperature resistance and the corrosion resistance are improved, and crystal form transformation is promoted; and silica sol, ethanol and polyethylene glycol are used for film formation to enhance adhesion, and silicon nitride and aluminum phosphate are added to improve high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating materials, and specifically refers to a high-performance crucible coating for large-diameter single-crystal silicon and a preparation method thereof. Background Art

[0002] As the core material in the growth process of single crystal silicon, quartz crucible needs to withstand high temperature and highly corrosive environment, while also having excellent thermal stability, thermal shock resistance and structural integrity.

[0003] In the existing technology, quartz crucible coatings are mostly made of single materials such as silicon nitride and silicon carbide. Although they have certain high temperature resistance, they have obvious limitations. First, in high temperature environments, the thermal stress distribution of these traditional coating materials is uneven, which makes the quartz crucible prone to bulging or cracking; second, when preparing single crystal silicon, the quartz crucible is easily corroded by oxygen and impurities, showing insufficient corrosion resistance and shortening the service life; third, the interface bonding strength between the coating and the quartz crucible substrate is low, and it is easy to peel off or fall off; finally, the existing coating preparation process is complicated and costly, and cannot meet the needs of large-scale production.

[0004] Therefore, preparing a high-performance crucible coating for large-diameter single crystal silicon to improve the temperature resistance, corrosion resistance and structural stability of the quartz crucible has become a key technical problem that needs to be urgently solved in the photovoltaic industry. Summary of the invention

[0005] In order to overcome the defects of the prior art, the high-performance crucible coating for large-diameter single crystal silicon prepared by the present invention adopts Al2O3 and boron nitride co-heating method to prepare aluminum nitride as the main material for the first time, and introduces excessive carbon powder. On the one hand, the strength of the coating can be enhanced at high temperature and the thermal conductivity of the coating can be improved to avoid the coating from falling off due to uneven thermal conductivity. On the other hand, carbon reacts with aluminum nitride to form Al-C bonds, which not only significantly enhances the high-temperature resistance of the material, but also inhibits crystal slip deformation by hindering dislocation movement, thereby improving the high-temperature structural stability. The uniform distribution of carbon makes the thermal stress distribution more uniform, thereby preventing the quartz crucible from bulging or cracking due to uneven heat. The CN bonds formed between the Al-C bonds and the Al-N bonds can enhance the bonding force between atoms, thereby making the coating harder, more wear-resistant and more tough. In order to further improve the performance, The surface of the aluminum nitride-carbon composite material is rich in hydroxyl groups after alcoholization treatment. It is treated with a silane coupling agent to condense with the hydroxyl groups to improve the surface adsorption. At the same time, magnesium powder is introduced to remove oxygen to generate MgO, which improves the heat resistance and corrosion resistance of the coating. MgO acts as a nucleating agent to promote the crystal transformation of the quartz crucible, further improving the overall heat resistance. In addition, in order to enhance the adhesion and structural stability, the silica sol is mixed with anhydrous ethanol, and ethanol adjusts the viscosity and surface tension to form a continuous and uniform film layer. Polyethylene glycol is added to reduce the surface tension, improve wettability and adhesion, and form a network structure to enhance flexibility and integrity. Aluminum phosphate is introduced to utilize the characteristics of aluminum phosphate filling the gaps to densify the structure. The decomposition of aluminum phosphate provides a protective film for the coating, improves the high-temperature corrosion resistance, and forms a more stable high-temperature phase at high temperatures, which significantly improves the high-temperature resistance of the coating.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is a high-performance crucible coating for large-diameter single crystal silicon, which is prepared from the following raw materials in parts by weight: 10-15 parts of coating compound, 5-8 parts of composite colloid, 1 part of magnesium powder, 2-5 parts of SiC and 0.5 parts of quartz fiber.

[0007] Furthermore, the preparation method of the complex A comprises the following steps:

[0008] (a) weighing 1-2 parts of Al2O3, 4-8 parts of boron nitride and 0.3 parts of flux, grinding and mixing to obtain a reactant precursor;

[0009] (b) placing the reactant precursor obtained in step (a) into a calcining furnace with an argon gas flow rate of 0.5 L / min, heat-treating it at a temperature of 1600-1800° C. for 6 hours, and then cooling it naturally to room temperature to obtain an aluminum nitride composite A;

[0010] (c) Weigh 0.2-0.5 parts of carbon powder and add it to the aluminum nitride composite A obtained in step (b), grind it evenly, put it into a calcining furnace with an argon flow rate of 0.5 L / min, heat treat it at a temperature of 1800-2000°C for 6 hours, and then cool it naturally to room temperature to obtain composite A.

[0011] Furthermore, the flux is GaO.

[0012] Furthermore, the method for preparing the coating composite comprises the following steps:

[0013] (α) Weighing 3-5 parts of the complex A, adding it to 0.5-1.5 parts of the mixed alcohol, stirring at a speed of 500-800 r / min for 30 minutes, to obtain a mixed solution A;

[0014] (β) Add 1 part of silane coupling agent to the mixed solution A obtained in step (α), stir at a speed of 500-800 r / min for 30 min, heat at a temperature of 60-90° C. for 2 h, and stand at room temperature for 72 h to obtain a coating composite.

[0015] Furthermore, the mixed alcohol is a mixture of silanol and anhydrous ethanol, and the weight ratio of the silanol to the anhydrous ethanol is 1-2:3.

[0016] Furthermore, the preparation method of the composite colloid comprises the following steps:

[0017] (i) Weighing 6-10 parts of anhydrous ethanol and 4-8 parts of silica sol, mixing and stirring at a speed of 500-800 r / min for 30 minutes to obtain a homogeneous solution A;

[0018] (ii) adding 1-2 parts of polyethylene glycol to the homogenous solution A obtained in step (i), and stirring at a speed of 300-500 r / min for 30 min to obtain a mixed solution I;

[0019] (iii) weighing 0.3-0.6 parts of silicon nitride and 1 part of aluminum phosphate, mixing and grinding, sieving with a 40-mesh screen to obtain a mixture I, adding the obtained mixture I to the mixed solution I obtained in step (ii), and ultrasonically treating for 30 minutes at an ultrasonic power of 0.3-0.5 kW to obtain a colloidal suspension;

[0020] (iv) heating the colloidal suspension obtained in step (iii) to 50° C. and ripening for 12 h, and then sealing and storing to obtain a composite colloidal material.

[0021] The present invention also provides a method for preparing a high-performance crucible coating for large-diameter single crystal silicon, comprising the following steps:

[0022] Step 1, weigh 2-5 parts of SiC and add them to 5-8 parts of the composite colloid, ultrasonicate for 30 minutes at an ultrasonic power of 0.8-1.2 kW, and stir for 30 minutes at a rotation speed of 500-800 r / min to obtain a substrate;

[0023] Step 2: Weigh 10-15 parts of the coating compound and 0.5 parts of quartz fiber and add them to the substrate obtained in step 1, heat at a temperature of 80-120° C. for 2 hours, and stir at a speed of 300-500 r / min to obtain a high-performance crucible coating precursor for large-diameter single crystal silicon;

[0024] Step three, deoxygenate the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two at a flow rate of argon at 300 ml / min for 2 hours, weigh 1 part of magnesium powder and add it to the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two, ultrasonically treat it for 20 minutes at an ultrasonic power of 0.3-0.6 kW, and stir it for 30 minutes at a speed of 300-500 r / min, fill it with argon protective gas and seal it to obtain a high-performance crucible coating for large-diameter single-crystalline silicon.

[0025] The beneficial effects achieved by the present invention are as follows:

[0026] The high-performance crucible coating for large-diameter single-crystal silicon prepared by the present invention adopts a co-heating method of Al2O3 and boron nitride to prepare aluminum nitride, which is used as the main material of the coating. It has high strength and does not introduce impurities into the preparation of single-crystal silicon. On this basis, excessive carbon powder is introduced. In a high-temperature environment, the carbon powder can significantly enhance the mechanical strength of the coating, and at the same time greatly improve the thermal conductivity of the coating. The uniform thermal conductivity characteristics effectively avoid the problem of coating shedding caused by uneven thermal conductivity. Moreover, carbon powder reacts with aluminum nitride at high temperature to generate Al-C bonds. The formation of this chemical bond not only greatly enhances the material's resistance to high temperature, but also effectively hinders dislocation movement and inhibits the slip deformation of crystals at high temperatures, thereby effectively improving the structural stability of the coating in high temperature environments. In addition, the introduction of carbon powder allows thermal stress to be more evenly dispersed, avoiding bulging or cracking of the quartz crucible due to local heat concentration. On the basis of forming Al-C bonds, Al-N bonds further react with Al-C bonds to generate CN bonds. The presence of CN bonds significantly enhances the bonding force between atoms, giving the coating higher hardness, excellent wear resistance and good toughness, effectively improving the overall mechanical properties of the coating.

[0027] The high-performance crucible coating for large-diameter single crystal silicon prepared by the present invention is subjected to alcoholization treatment on the aluminum nitride-carbon composite material in order to further explore the performance potential of the coating, so that the surface of the material is rich in a large number of hydroxyl groups; then, it is treated with a silane coupling agent, and the silane coupling agent reacts with the hydroxyl groups on the surface to significantly improve the adsorption performance of the coating surface. At the same time, magnesium powder is introduced, and the magnesium powder reacts with the oxygen generated in the single crystal preparation process to generate MgO; the generation of MgO not only improves the high temperature resistance and corrosion resistance of the coating, but also because of its characteristics as a nucleating agent, it can promote the crystal transformation of the quartz crucible, improve the mechanical strength of the quartz crucible, and prevent edge collapse.

[0028] The high-performance crucible coating for large-diameter single-crystal silicon prepared by the present invention, in terms of enhancing the adhesion and structural stability of the coating, the silica sol is mixed with anhydrous ethanol, the anhydrous ethanol can effectively adjust the viscosity and surface tension of the mixed solution, so that the solution can form a continuous and uniform film layer on the surface of the substrate, and polyethylene glycol is added thereto, the polyethylene glycol can further reduce the surface tension, significantly improve the wettability and adhesion of the coating, and at the same time form a network structure inside the coating, thereby enhancing the flexibility and integrity of the coating; in addition, the key component of aluminum phosphate is introduced, and aluminum phosphate can fully fill the gaps inside the coating, making the coating structure denser; under high temperature conditions, the decomposition of aluminum phosphate will form a dense protective film on the surface of the coating, effectively improving the high-temperature corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A diagram showing a method for preparing a high-performance crucible coating for large-diameter single-crystal silicon proposed by the present invention;

[0030] Figure 2 The corrosion rate diagram of the high performance crucible coating for large diameter single crystal silicon prepared in the examples and comparative examples;

[0031] Figure 3 The deoxidation rate diagram of the high-performance crucible coating for large-diameter single crystal silicon prepared in the examples and comparative examples.

[0032] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0035] The preparation methods in the following examples are referred to Figure 1 , unless otherwise specified, all methods are conventional; unless otherwise specified, the purity of the materials used in the following examples is 99.999%, the parts are calculated by mass, and the materials used are new materials purchased from the market.

[0036] Example 1: A high-performance crucible coating for large-diameter single-crystal silicon is prepared from the following raw materials in parts by weight: 10 parts of coating compound, 5 parts of composite colloid, 1 part of magnesium powder, 2 parts of SiC and 0.5 parts of quartz fiber.

[0037] The preparation method of compound A comprises the following steps:

[0038] (a) weighing 1 part of Al2O3, 4 parts of boron nitride and 0.3 parts of GaO, grinding and mixing them to obtain a reactant precursor;

[0039] (b) placing the reactant precursor obtained in step (a) into a calcining furnace with an argon gas flow rate of 0.5 L / min, heat-treating it at a temperature of 1600° C. for 6 hours, and then naturally cooling it to room temperature to obtain an aluminum nitride composite A;

[0040] (c) Weigh 0.2 parts of carbon powder and add it to the aluminum nitride composite A obtained in step (b) and grind it evenly. Put it into a calcining furnace with an argon flow rate of 0.5 L / min, heat treat it at a temperature of 1800°C for 6 hours, and then cool it naturally to room temperature to obtain composite A.

[0041] The method for preparing the coating composite comprises the following steps:

[0042] (α) Weighing 3 parts of the complex A, adding it to 0.5 parts of a mixed alcohol, wherein the mixed alcohol is a mixture of silanol and anhydrous ethanol, the mass ratio of the silanol to the anhydrous ethanol is 1:3, stirring at a speed of 500 r / min for 30 minutes, to obtain a mixed solution A;

[0043] (β) Add 1 part of silane coupling agent to the mixed solution A obtained in step (α), stir at a rotation speed of 500 r / min for 30 min, heat at a temperature of 60° C. for 2 h, and stand at room temperature for 72 h to obtain a coating composite.

[0044] The preparation method of the composite colloid comprises the following steps:

[0045] (i) Weighing 6 parts of anhydrous ethanol and 4 parts of silica sol, mixing and stirring at a speed of 500 r / min for 30 min to obtain a homogeneous solution A;

[0046] (ii) adding 1 part of polyethylene glycol to the homogenous solution A obtained in step (i), and stirring at a rotation speed of 300 r / min for 30 min to obtain a mixed solution I;

[0047] (iii) weighing 0.3 parts of silicon nitride and 1 part of aluminum phosphate, mixing and grinding, sieving with a 40-mesh screen to obtain a mixture I, adding the obtained mixture I to the mixed solution I obtained in step (ii), and ultrasonically treating for 30 minutes at an ultrasonic power of 0.3 kW to obtain a colloidal suspension;

[0048] (iv) heating the colloidal suspension obtained in step (iii) to 50° C. and ripening for 12 h, and then sealing and storing to obtain a composite colloidal material.

[0049] This embodiment also provides a method for preparing a high-performance crucible coating for large-diameter single crystal silicon, comprising the following steps:

[0050] Step 1, weigh 2 parts of SiC and add them to 5 parts of the composite colloid, ultrasonicate for 30 minutes at an ultrasonic power of 0.8 kW, and stir for 30 minutes at a rotation speed of 500 r / min to obtain a substrate;

[0051] Step 2: Weigh 10 parts of the coating compound and 0.5 parts of quartz fiber and add them to the substrate obtained in step 1, heat at 80° C. for 2 hours, and stir at a speed of 300 r / min to obtain a high-performance crucible coating precursor for large-diameter single crystal silicon;

[0052] Step three, deoxygenate the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two at a flow rate of argon at 300 ml / min for 2 hours, weigh 1 part of magnesium powder and add it to the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two, ultrasonically treat it for 20 minutes at an ultrasonic power of 0.3 kW, and stir it for 30 minutes at a speed of 300 r / min, fill it with argon protective gas and seal it to obtain a high-performance crucible coating for large-diameter single-crystalline silicon.

[0053] Example 2: A high-performance crucible coating for large-diameter single-crystal silicon is prepared from the following raw materials in parts by weight: 13 parts of coating compound, 6.5 parts of composite colloid, 1 part of magnesium powder, 3.5 parts of SiC and 0.5 parts of quartz fiber.

[0054] The preparation method of compound A comprises the following steps:

[0055] (a) weighing 1 part of Al2O3, 4 parts of boron nitride and 0.3 parts of GaO, grinding and mixing them to obtain a reactant precursor;

[0056] (b) placing the reactant precursor obtained in step (a) into a calcining furnace with an argon gas flow rate of 0.5 L / min, heat-treating it at a temperature of 1700° C. for 6 hours, and then naturally cooling it to room temperature to obtain an aluminum nitride composite A;

[0057] (c) Weigh 0.35 parts of carbon powder and add it to the aluminum nitride composite A obtained in step (b) and grind it evenly. Put it into a calcining furnace with an argon flow rate of 0.5 L / min, heat treat it at a temperature of 1900°C for 6 hours, and then cool it naturally to room temperature to obtain composite A.

[0058] The method for preparing the coating composite comprises the following steps:

[0059] (α) Weighing 4 parts of the complex A and adding it to 1 part of a mixed alcohol, wherein the mixed alcohol is a mixture of silanol and anhydrous ethanol, wherein the weight ratio of the silanol to the anhydrous ethanol is 1.5:3, and stirring at a rotation speed of 650 r / min for 30 minutes to obtain a mixed solution A;

[0060] (β) Add 1 part of silane coupling agent to the mixed solution A obtained in step (α), stir at a rotation speed of 650 r / min for 30 min, heat at a temperature of 75° C. for 2 h, and stand at room temperature for 72 h to obtain a coating composite.

[0061] The preparation method of the composite colloid comprises the following steps:

[0062] (i) 8 parts of anhydrous ethanol and 6 parts of silica sol were weighed and mixed and stirred at a speed of 650 r / min for 30 min to obtain a homogeneous solution A;

[0063] (ii) adding 1.5 parts of polyethylene glycol to the homogenous solution A obtained in step (i), and stirring at a rotation speed of 400 r / min for 30 min to obtain a mixed solution I;

[0064] (iii) weighing 0.45 parts of silicon nitride and 1 part of aluminum phosphate, mixing and grinding, sieving with a 40-mesh screen to obtain a mixture I, adding the obtained mixture I to the mixed solution I obtained in step (ii), and ultrasonically treating for 30 minutes at an ultrasonic power of 0.4 kW to obtain a colloidal suspension;

[0065] (iv) heating the colloidal suspension obtained in step (iii) to 50° C. and ripening for 12 h, and then sealing and storing to obtain a composite colloidal material.

[0066] This embodiment also provides a method for preparing a high-performance crucible coating for large-diameter single crystal silicon, comprising the following steps:

[0067] Step 1, weigh 3.5 parts of SiC and add it to 6.5 parts of the composite colloid, ultrasonicate for 30 minutes at an ultrasonic power of 1.0 kW, and stir for 30 minutes at a rotation speed of 650 r / min to obtain a substrate;

[0068] Step 2: Weigh 13 parts of the coating compound and 0.5 parts of quartz fiber, add them to the substrate obtained in step 1, heat at 100° C. for 2 hours, and stir at a speed of 400 r / min to obtain a high-performance crucible coating precursor for large-diameter single crystal silicon;

[0069] Step three, deoxygenate the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two at a flow rate of argon at 300 ml / min for 2 hours, weigh 1 portion of magnesium powder and add it to the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two, ultrasonically treat for 20 minutes at an ultrasonic power of 0.45 kW, and stir for 30 minutes at a speed of 450 r / min, fill with argon protective gas and seal for storage, to obtain a high-performance crucible coating for large-diameter single-crystalline silicon.

[0070] Example 3: A high-performance crucible coating for large-diameter single-crystal silicon is prepared from the following raw materials in parts by weight: 15 parts of coating compound, 8 parts of composite colloid, 1 part of magnesium powder, 5 parts of SiC and 0.5 parts of quartz fiber.

[0071] The preparation method of compound A comprises the following steps:

[0072] (a) weighing 2 parts of Al2O3, 8 parts of boron nitride and 0.3 parts of GaO, grinding and mixing them to obtain a reactant precursor;

[0073] (b) placing the reactant precursor obtained in step (a) into a calcining furnace with an argon gas flow rate of 0.5 L / min, heat-treating it at a temperature of 1800° C. for 6 h, and then naturally cooling it to room temperature to obtain an aluminum nitride composite A;

[0074] (c) Weigh 0.5 parts of carbon powder and add it to the aluminum nitride composite A obtained in step (b) and grind it evenly. Put it into a calcining furnace with an argon flow rate of 0.5 L / min, heat treat it at a temperature of 2000°C for 6 hours, and then cool it naturally to room temperature to obtain composite A.

[0075] The method for preparing the coating composite comprises the following steps:

[0076] (α) Weighing 5 parts of the complex A, adding it to 1.5 parts of a mixed alcohol, wherein the mixed alcohol is a mixture of silanol and anhydrous ethanol, the mass ratio of the silanol to the anhydrous ethanol is 2:3, stirring at a speed of 800 r / min for 30 minutes, to obtain a mixed solution A;

[0077] (β) Add 1 part of silane coupling agent to the mixed solution A obtained in step (α), stir at a speed of 800 r / min for 30 min, heat at 90° C. for 2 h, and stand at room temperature for 72 h to obtain a coating composite.

[0078] The preparation method of the composite colloid comprises the following steps:

[0079] (i) 10 parts of anhydrous ethanol and 8 parts of silica sol were weighed and mixed and stirred at a speed of 800 r / min for 30 min to obtain a homogeneous solution A;

[0080] (ii) adding 2 parts of polyethylene glycol to the homogenous solution A obtained in step (i), and stirring at a speed of 500 r / min for 30 min to obtain a mixed solution I;

[0081] (iii) weighing 0.6 parts of silicon nitride and 1 part of aluminum phosphate, mixing and grinding, sieving with a 40-mesh screen to obtain a mixture I, adding the obtained mixture I to the mixed solution I obtained in step (ii), and ultrasonically treating for 30 minutes at an ultrasonic power of 0.5 kW to obtain a colloidal suspension;

[0082] (iv) heating the colloidal suspension obtained in step (iii) to 50° C. and ripening for 12 h, and then sealing and storing to obtain a composite colloidal material.

[0083] This embodiment also provides a method for preparing a high-performance crucible coating for large-diameter single crystal silicon, comprising the following steps:

[0084] Step 1, weigh 5 parts of SiC and add them to 8 parts of the composite colloid, ultrasonicate for 30 minutes at an ultrasonic power of 1.2 kW, and stir for 30 minutes at a rotation speed of 800 r / min to obtain a substrate;

[0085] Step 2: Weigh 15 parts of the coating compound and 0.5 parts of quartz fiber and add them to the substrate obtained in step 1, heat at a temperature of 120° C. for 2 hours, and stir at a speed of 500 r / min to obtain a high-performance crucible coating precursor for large-diameter single crystal silicon;

[0086] Step three, deoxygenate the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two at a flow rate of argon at 300 ml / min for 2 hours, weigh 1 portion of magnesium powder and add it to the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step two, ultrasonicate for 20 minutes at an ultrasonic power of 0.6 kW, and stir for 30 minutes at a speed of 500 r / min, fill with argon protective gas and seal for storage, to obtain a high-performance crucible coating for large-diameter single-crystalline silicon.

[0087] Comparative Example:

[0088] The difference between Comparative Example 1 and Example 2 is that no coating composite is added, and the rest is the same as Example 2;

[0089] The difference between Comparative Example 2 and Example 2 is that quartz fiber is not added, and the rest is the same as Example 2;

[0090] The difference between Comparative Example 3 and Example 2 is that no magnesium powder is added, and the rest is the same as Example 2;

[0091] Comparative Example 4 is a common quartz crucible without further treatment.

[0092] The performance of the high-performance crucible coating for large-diameter single crystal silicon prepared by the test is analyzed as follows:

[0093] First, the surface of the quartz crucible is polished and wiped, and then the prepared large-diameter single crystal silicon high-performance crucible coating is uniformly deposited on the outer surface of the quartz crucible by chemical vapor deposition, and the thickness of the spray coating is 150-200 μm. Then, it is placed in a single crystal furnace, and 15L / min argon gas is introduced for solidification and storage for 72 hours to obtain a quartz crucible coated with a large-diameter single crystal silicon high-performance crucible coating; then, the obtained quartz crucible coated with a large-diameter single crystal silicon high-performance crucible coating is placed in a furnace for preparing a single crystal. This product is a 12-inch n-type single crystal silicon, and the average oxygen content of the n-type single crystal silicon wafer is 10.5ppma. The test range of oxygen involved in this embodiment is to remove 1000mm from the head and tail of a complete single crystal silicon rod (length greater than 3500mm and above), and perform a slice test on the silicon rod in the middle;

[0094] Table 1 shows the shedding conditions of the coatings in the examples and comparative examples:

[0095]

[0096] It can be seen from Table 1 that the high-performance crucible coating for large-diameter single crystal silicon prepared in Example 1 had partial peeling off of the surface coating after 550 hours of single crystal preparation, the coating obtained in Example 2 did not fall off, and the coating obtained in Example 3 was partially corroded. The high-performance crucible coating for large-diameter single crystal silicon prepared in the comparative examples, among which Comparative Examples 1 and Comparative Examples 2 had coating shedding and bubbles after 450 hours of use and were retired, while the ordinary quartz crucible had corrosion and bubbling after 350 hours of use and was retired. It can be seen from the above results that the high-performance crucible coating for large-diameter single crystal silicon prepared in Example 2 has high corrosion resistance and high temperature resistance, which prolongs the service life and reduces the cost in the large-diameter single crystal silicon preparation process.

[0097] Figure 2 The corrosion rate test of the high-performance crucible coating for large-diameter single-crystal silicon prepared in the examples and comparative examples during use, wherein the average corrosion rate of Example 2 in the first 200 hours is 0.082 microns / hour, the average corrosion rate in 200-450 hours is 0.037 microns / hour, and the average corrosion rate in 450-550 hours is 0.025 microns / hour. It can be seen that the high-performance crucible coating for large-diameter single-crystal silicon prepared in Example 2 has good corrosion resistance, which is crucial for protecting the quartz crucible, and the corrosion rate is significantly lower than other values ​​compared with other examples and comparative examples; Figure 3 The deoxygenation rate of single crystal silicon wafers pulled by the high-performance crucible coating for large-diameter single crystal silicon prepared in the examples and comparative examples, wherein the deoxygenation rate of the first rod in Example 2 is 20.4%, the deoxygenation rate of the second rod is 19.7%, and the deoxygenation rate of the third rod is 19.1%. It can be seen that the prepared high-performance crucible coating for large-diameter single crystal silicon has a certain effect on the control of oxygen in the single crystal, and the difference in deoxygenation rate is not large, indicating that the introduction of magnesium powder plays a certain role in deoxygenation.

[0098] Obviously, the above comparative examples and embodiments are only a part of comparative examples and embodiments of the present invention, and they and the comparative examples and embodiments based on such references are all within the scope of protection of the present invention.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0100] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-performance crucible coating for large-diameter single crystal silicon, characterized in that: The invention comprises the following raw materials in parts by weight: 10-15 parts of coating compound, 5-8 parts of composite colloid, 1 part of magnesium powder, 2-5 parts of SiC and 0.5 parts of quartz fiber; The raw materials for preparing the coating composite are composed of composite A, mixed alcohol and silane coupling agent, the mass ratio of composite A, mixed alcohol and silane coupling agent is 3-5:0.5-1.5:1, the raw materials for preparing the composite A are composed of Al2O3, boron nitride, flux and carbon powder, the mass ratio of Al2O3, boron nitride, flux and carbon powder is 1-2:4-8:0.3:1.5-2.5; The raw materials for preparing the composite colloid are composed of anhydrous ethanol, silica sol, polyethylene glycol, silicon nitride and aluminum phosphate, and the mass proportion of the anhydrous ethanol, silica sol, polyethylene glycol, silicon nitride and aluminum phosphate is 6-10:4-8:1-2:0.3-0.6:

1.

2. The high-performance crucible coating for large-diameter single crystal silicon according to claim 1, characterized in that: The method for preparing the coating composite comprises the following steps: (α) Weighing the complex A, adding it to the mixed alcohol, stirring, and obtaining a mixed solution A; (β) Adding a silane coupling agent to the mixed solution A obtained in step (α), stirring and heating, and allowing the mixture to stand to obtain a coating composite.

3. The high-performance crucible coating for large-diameter single crystal silicon according to claim 2, characterized in that: The mixed alcohol product in step (α) is a mixture of silanol and anhydrous ethanol, and the mass ratio of the silanol to the anhydrous ethanol is 1-2:

3.

4. The high-performance crucible coating for large-diameter single crystal silicon according to claim 1, characterized in that: The preparation method of the composite colloid comprises the following steps: (i) weighing anhydrous ethanol and silica sol, mixing and stirring to obtain a homogeneous solution A; (ii) adding polyethylene glycol to the homogenous solution A obtained in step (i), stirring, to obtain a mixed solution I; (iii) weighing silicon nitride and aluminum phosphate, mixing and grinding, and sieving to obtain a mixture I, adding the obtained mixture I to the mixed solution I obtained in step (ii), and ultrasonically treating to obtain a colloidal suspension; (iv) ripening the colloidal suspension obtained in step (iii), and sealing to obtain a composite colloidal material.

5. The high-performance crucible coating for large-diameter single crystal silicon according to claim 1, characterized in that: The preparation method of the complex A comprises the following steps: (a) weighing Al2O3, boron nitride and flux, grinding and mixing them to obtain a reactant precursor; (b) heat treating the reactant precursor obtained in step (a), and cooling to room temperature to obtain an aluminum nitride composite A; (c) Weighing carbon powder, adding it to the aluminum nitride composite A obtained in step (b), grinding it evenly, heat treating it, and cooling it to room temperature to obtain composite A.

6. The high-performance crucible coating for large-diameter single crystal silicon according to claim 5, characterized in that: The flux described in step (a) is GaO.

7. A method for preparing a high-performance crucible coating for large-diameter single crystal silicon according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, weighing SiC and adding it to the composite colloid, ultrasonicating and stirring to obtain a substrate; Step 2: weighing the coating compound and quartz fiber and adding them to the substrate obtained in step 1, heating and stirring to obtain a high-performance crucible coating precursor for large-diameter single crystal silicon; Step 3: introduce argon gas into the high-performance crucible coating precursor for large-diameter single-crystalline silicon obtained in step 2, weigh magnesium powder and add it thereto, perform ultrasonication and stirring, and obtain a high-performance crucible coating for large-diameter single-crystalline silicon.

Citation Information

Patent Citations

  • Silicon-based ceramic coatings for quartz crucibles for czochralski growth of silicon single crystals, similar unidirectional growth methods and similar semiconductor materials, and other applications requiring reduced chemical reactivity of fused silica

    CA2475212A1

  • Silicon nitride combined silicon carbide composite barium coating quartz crucible and preparation method thereof

    CN109627047A

  • Preparation method of high-performance aluminum nitride material

    CN114380279A

  • Silicon nitride crystal based on physical vapor transport method and preparation method thereof

    CN119615355A

  • Method for preparing aluminium nitride powder by carbothermic reduction method

    CN1631772A